2010
DOI: 10.1128/jb.01459-09
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide as Shield and Receptor for R-Pyocin-Mediated Killing in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa produces three different types of bacteriocins: the soluble S-pyocins and the bacteriophage-like F-and R-pyocins. R-pyocins kill susceptible bacteria of the same or closely related species with high efficiency. Five different types of R-pyocins (R1-to R5-pyocins) have been described based on their killing spectra and tail fiber protein sequences. We analyzed the distribution of R-pyocin genes in a collection of clinical P. aeruginosa isolates. We found similar percentages of isolates not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
195
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(202 citation statements)
references
References 27 publications
7
195
0
Order By: Relevance
“…akhurstii RM1 displayed low sensitivity. These findings show that xenorhabdicin activity is not dictated by bacterial or nematode phylogeny and suggest that sensitivity to xenorhabdicin is determined by structural components of the LPS receptor molecule (18). If this were the case, then the structure of LPS of sensitive strains would be predicted to be similar, while the LPS structure of less sensitive strains would be more divergent.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…akhurstii RM1 displayed low sensitivity. These findings show that xenorhabdicin activity is not dictated by bacterial or nematode phylogeny and suggest that sensitivity to xenorhabdicin is determined by structural components of the LPS receptor molecule (18). If this were the case, then the structure of LPS of sensitive strains would be predicted to be similar, while the LPS structure of less sensitive strains would be more divergent.…”
Section: Discussionmentioning
confidence: 86%
“…They are composed of an outer sheath, an inner tube, and associated tail fibers. R-type pyocins bind via tail fibers to lipopolysaccharide (LPS) receptors on the surface of sensitive bacteria (18,24,27,40). It has been shown that recombination of tail fiber proteins broadens R-type bacteriocin specificity (24).…”
mentioning
confidence: 99%
“…LPS has been linked to antibiotic resistance and immune evasion. Furthermore, LPS is one of the receptors that determines the susceptibility of the bacterium to bacteriophages and pyocins (2)(3)(4). Our ability to control P. aeruginosa infections depends on the availability of accurate typing methods.…”
mentioning
confidence: 99%
“…The soluble S-type is similar to colicins of E. coli and is composed of killing and immunity genes. While the R and F type are phage-derived and have different killing and resistance mechanisms, where both consist of only a killing component with no specified immunity that neutralizes the toxin but instead resist via alteration or absence of cell-surface receptors [2,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, in natural populations of bacteria like P. aeruginosa one strain usually carries and releases multiple types of bacteriocins known as pyocins, which have a diversity of killing and resistance mechanisms in addition to the toxinantitoxin systems [2,7]. For example, three pyocin types exist (S, R and F), with each of these having multiple subtypes with varying toxicity levels [2,[7][8][9][10]. The soluble S-type is similar to colicins of E. coli and is composed of killing and immunity genes.…”
Section: Introductionmentioning
confidence: 99%